1996
DOI: 10.1002/pc.10641
|View full text |Cite
|
Sign up to set email alerts
|

Braided thermoplastic composites from powder‐coated towpregs. Part III: Consolidation and mechanical properties

Abstract: Carbon fiber/nylon 6 powder coated and commingled tows were braided into biaxial braids with a ±45° braid angle. Consolidation experiments were carried out to study the influence of consolidation conditions on the properties of the laminates using a 23 full factorial experimental design. The consolidation studies reveal that commingled tows require more severe consolidation conditions than powder coated tows to obtain comparable properties. The dependence of powder‐coated laminate qualities like void content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…In the early 1970s, Chwastiak13 introduced a procedure for wicking rate measurement by enclosing a carbon fiber bundle in a glass tube so that the porosity was fixed for a given strand of carbon fibers. This procedure has been used successfully to evaluate the wettability of carbon yarn by water, glycol, heptane 14. The contact angle used in this investigation is calculated by the eq.…”
Section: Resultsmentioning
confidence: 99%
“…In the early 1970s, Chwastiak13 introduced a procedure for wicking rate measurement by enclosing a carbon fiber bundle in a glass tube so that the porosity was fixed for a given strand of carbon fibers. This procedure has been used successfully to evaluate the wettability of carbon yarn by water, glycol, heptane 14. The contact angle used in this investigation is calculated by the eq.…”
Section: Resultsmentioning
confidence: 99%
“…Summarizing all the results, they concluded that the air-textured commingled yarns with optimized fiber sizing provide the highest transverse modulus and strength, as well as the higher crack resistance [8]. Ramasamy et al [10,11] have studied braided thermoplastic composites from carbon fiber/polyamide 6 powder-coated yarns and also the influence of the consolidation conditions on the laminate properties. The impregnation of fabric structures with thermoplastic polyamide 6.6 in continuous manufacturing was accomplished along the direction of thickness rather than in-plane as usual in liquid composite manufacturing techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for forming CFRTPs have been studied. A commingle method involves placing the fabric made of commingled yarn of carbon and thermoplastic fibers in a mold, heating the mold to melt the thermoplastic, and applying pressure to impregnate the thermoplastic in the carbon fibers . Furthermore, a film‐stacking method involves placing a carbon fiber fabric and thermoplastic film alternately in between the rubber diaphragms and applying heat and pressure to impregnate the thermoplastic to the fabric .…”
Section: Introductionmentioning
confidence: 99%